Program Bimbingan untuk Meningkatkan Kecakapan Self Direction Mahasiswa - El Fiah, Rifda (Universitas Islam Negeri Raden Intan Lampung, 2017)
This research leads to the formation of self-guidance and academic guidance counseling program by academic advisors in assisting students to develop self-directed skills so that they can learn and lecture on campus effectively, so that universities can produce high achieving and qualified graduates as well always able to develop itself in accordance with the demands of the profession, the change of society, and the dynamics of life. This study uses descriptive approach, which aims to explain a situation in a systematic or explaining a particular field that became the center of the researcher's attention in factual and thorough, namely the dimensions of self-direction skills that should be owned by students in order to undergo the process of lectures and effective learning on campus UIN Raden Intan Lampung. The respondents involved 20 lecturers and 130 students. The results of this study indicate that more than 50% of college students have low self-directed skills. Therefore, the lecturers are expected to have possess and master the guidance material, able to grow and develop students' self-confidence, able to communicate effectively and empathetically with the students, and always motivate the students, and develop positive, innovative and open attitude with the students.